1975
DOI: 10.1136/bmj.1.5957.546
|View full text |Cite
|
Sign up to set email alerts
|

Serum ferritin assay and iron status in chronic renal failure and haemodialysis.

Abstract: 546BRITISH MEDICAL JOURNAL 8 MARCH 1975 noted that electron-dense deposits in electronmicrographs were usually on the "endothelial surface of the glomerular capillary wall." Such lesions were clearly not among those we saw.With regard to the relationship between Q.M.N. and the tropical nephropathy seen in Senegal the similarities lie in the histological features rather than in the immunofluorescence findings. Thus in both conditions a fibrillary change in the capillary wall leads to focal and segmental glome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
40
1
3

Year Published

1977
1977
2008
2008

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(45 citation statements)
references
References 7 publications
(1 reference statement)
1
40
1
3
Order By: Relevance
“…Their performance is similarly poor in populations of patients with inflammatory rheumatic disease, 26 hematologic malignancies, 18 or chronic renal failure. 12 We suggest that there is abundant evidence from studies in patients with inflammation, infection, maligancy, or chronic renal failure and growing evidence from studies in patients with unselected acute and chronic illnesses that transferrin saturation and TIBC can be eliminated from the evaluation of microcytic or normocytic anemia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Their performance is similarly poor in populations of patients with inflammatory rheumatic disease, 26 hematologic malignancies, 18 or chronic renal failure. 12 We suggest that there is abundant evidence from studies in patients with inflammation, infection, maligancy, or chronic renal failure and growing evidence from studies in patients with unselected acute and chronic illnesses that transferrin saturation and TIBC can be eliminated from the evaluation of microcytic or normocytic anemia.…”
Section: Discussionmentioning
confidence: 99%
“…[4][5][6][7][8][9][10][11][12] Numerous studies have evaluated the efficacy of serum iron indicators as gauges of iron stores in anemic patients with these chronic diseases. A number of these studies have correlated serum iron measures with bone marrow hemosiderin (Table 1).…”
mentioning
confidence: 99%
“…20 Ferritin levels >600 ng/mL in dialysis-dependent CKD patients are associated with evidence of a reciprocal elevation of lipid peroxidation and depression of antioxidant defense. 80 The higher the dose of intravenous iron administered to dialysis patients, the greater the total body iron burden, the higher the serum ferritin level, 83 and the greater the evidence of oxidant stress. 80,84 Persistent oxidative stress in CKD patients promotes inflammation and, in turn, tissue injury, atherogenesis, and increased cardiovascular morbidity and mortality.…”
Section: Dosing Of Intravenous Iron Formulationsmentioning
confidence: 99%
“…SF is known as an indirect index of total body iron stores in healthy individuals and uremic patients on dialy sis [29][30][31][32][33]. From quantitative phlebotomy studies, many authors have advocated that iron stores demonstrated an exponential relationship with the SF [12-14, 34, 35].…”
Section: Iron Needs In Hemodialysis Patients On Erythropoietin Therapymentioning
confidence: 99%